Exergy Assessment and Exergetic Resilience of the Large-Scale Gas Oil Hydrocracking Process - Luisa José Acosta-Esalas; Ángel Darío González-Delgado (Sci, 2025)
Fossil fuels remain essential to the world’s energy supply, but the decline in the quality of the oil extracted has increased the relevance of processes such as hydrocracking. Despite its potential, this process involves high energy consumption. In order to assess its efficiency, an exergy analysis of a conventional hydrocracking unit was carried out using Computer Aided Process Engineering (CAPE) tools. After simulations, the physical and chemical exergies of the input and output streams were calculated, which showed a remarkable energy efficiency of 98.76%, attributable to the high exergy content of the products obtained (171,243,917.70 MJ/h) compared to the residues generated (1,065,290.8 MJ/h). The most significant irreversibilities were found in the Recycle Gas Sweetening stage, while the lowest exergy efficiency, 87.16%, was observed in the Residual Gas Sweetening phase. By valorizing the waste, the overall efficiency of the process increased to 99.26%, which allowed for a 40% reduction in the total irreversibilities. Optimization of the stages with the highest unavoidable losses and better energy integration of the process are suggested to maximize its performance.